Behavioural and Acoustical Responses of Coastal Dolphins to Noisy Environments - Marley, Sarah Anne (Curtin University, 2017)
This thesis aimed to examine the behavioural and acoustical responses of coastal dolphins to noisy environments. A combination of monitoring techniques were employed, in the form of land-based theodolite-tracking and autonomous underwater acoustic recorders. First, the soundscape of dolphin habitats was described to identify prominent sound sources and spatio-temporal patterns. Dolphin responses to the most ubiquitous anthropogenic sound source – vessel traffic – were then assessed, revealing alterations to movement speeds, behavioural budgets, and whistle characteristics.